A Bipolar Transporter as an Efficient Green Fluorescent Emitter and Host for Red Phosphors in Multi‐ and Single‐Layer Organic Light‐Emitting Diodes. Issue 42 (3rd September 2014) - Ye, Jun; Chen, Zhan; Wang, Kai; An, Feifei; Yuan, Yi; Chen, Wencheng; Yang, Qingdan; Zhang, Xiaohong; Lee, Chun‐Sing
Abstract: Multifunctional donor–acceptor compound 4, 4′‐bis(dibenzothiophene‐ S, S ‐dioxide‐2‐yl)triphenylamine (DSTPA ) was obtained by linking a strongly electron‐withdrawing core and a strongly electron‐donating core with a biphenyl bridge in linear spatial alignment.DSTPA not only has suitable HOMO and LUMO levels for easily accepting both holes and electrons, it was also demonstrated to have a high fluorescence quantum yield of 0.98 and a high triplet energy level of 2.39 eV. Versatile applications ofDSTPA for bipolar transport, green fluorescent emission, and sensitizing a red phosphor were systematically investigated in a series of multi‐ and single‐layer organic light‐emitting devices. In traditional multilayer devices, it shows excellent performance both in an undoped fluorescent device (used as a green emitter and achieving maximum current and power efficiencies (CE and PE) of 12.6 cd A −1 and 9.4 Lm W −1, respectively) and in a red phosphorescent device (used as a host and achieving maximum CE and PE of 26.4 cd A −1 and 26.3 Lm W −1, respectively). Furthermore, DSTPA was also simultaneously used as an emitter, a hole transporter, and an electron transporter in a single‐layer device showing CE and PE of 5.1 cd A −1 and 4.7 Lm W −1, respectively. A single‐layer red phosphorescent device with efficiencies of 11.7 cd A −1 and 12.6 Lm W −1 was obtained by dopingDSTPA with a red phosphor. The performances of all of the devices in this work are comparable to the best of their corresponding classes in the literature. Abstract : Multifunctional organic semiconductor : Donor–acceptor compoundDSTPA was rationally designed and synthesized to be capable of versatile applications in single‐ and multilayer electroluminescent devices, for example, bipolar transport, efficient green fluorescent emission, and as an effective host for red phosphors such as [Ir(2‐phq)2 (acac)] (see figure). ITO: indium tin oxide, 2‐phq: 2‐phenylquinoline, acac: acetylacetonate.